INCIDENT LEVEL AND HISTOLOGICAL ANALYSIS OF GLAND POLYPS IN THE PARASOL CAVITY (International journal of artificial intelligence, 2026)
Nasal polyps are a risk factor for rhinosinusitis (CRSwNP), a disease characterized by subjective and objective clinical manifestations of sinonasal inflammation. Nasal polyps are inflammatory lesions that descend into the nasal airway, arise bilaterally and from the ethmoid sinus. Men are more affected than women, but so far no specific genetic or environmental factors have been strongly linked to this appearance. CRSwNP is often associated with asthma and allergic rhinitis. Only ~25-30% of all cases of chronic rhinosinusitis (CRS) have CRSwNP.